Electrographic lead I and V5 monitoring could have detected a missed left‐side pneumothorax intraoperatively - Chihjen Lee; Roya Yumul; Colby Vongchaichinsri; Kevin Tsai; Lena Wang (Annals of Noninvasive Electrocardiology, 2023)
Abstract We present an EKG monitoring strategy to detect pneumothorax during high‐risk surgery. In the literature, EKG changes and pneumothorax are well‐described. However, anesthesiologists only monitor lead II on a three‐lead EKG system in the operating room. In our case, there was only a subtle change in lead II for a left‐sided pneumothorax, which could have been easily missed. On the contrary, there was a marked QRS amplitude reduction and T wave flattening/inversion in lead I and V5. We recommend lead V5 be added to the continuous monitoring and lead I be periodically checked for surgeries known to potentially cause pneumothorax.